The Influence of Data Utilization and Supply Chain Digitalization on the Operational Efficiency of MSMEs: A Study in Lampung Province - Bursan, Rinaldi (Open Science and Technology, 2025)
Aims and Methods: This study aims to analyze the effect of data capability and supply chain capability on the operational efficiency of MSMEs in Lampung Province. The method used is a quantitative approach and multiple linear regression analysis involving simulated data from 200 respondents to test the relationship between variables.Results: The results of the analysis show that supply chain capability has a more dominant and significant influence on operational efficiency compared to data capability. Data capability contributes positively and significantly to improving operational efficiency, especially when integrated into the supply chain management process. The R Square value of 0.497 indicates that almost 50% of the variation in operational efficiency can be explained by the two independent variables. The results of the study support the Resource-Based View (RBV) perspective that internal resources such as data and efficient supply chain systems are determining factors for the competitiveness of MSMEs.Conclusion: The practical implications of this study encourage the need for a digitalization strengthening program and data-based logistics systems to support local MSMEs to be more adaptive in facing market competition. This study also recommends further studies with sectoral and longitudinal approaches to understand the long-term impact of digital integration on MSME business performance.